A Ceramic Rich Quaternary Composite Solid-State Electrolyte for Solid-State Lithium Metal Batteries. Issue 8 (1st August 2022) - Al-Salih, Hilal; Cui, Mengyang; Yim, Chae-Ho; Sadighi, Zoya; Yan, Shuo; Karkar, Zouina; Goward, Gillian R.; Baranova, Elena A.; Abu-Lebdeh, Yaser
Abstract : Solid-state lithium metal batteries are one of the most promising candidates to take over the traditional liquid-based lithium ion batteries as they not only allow us to circumvent safety issues but also boost energy density far over the current limits imposed by the present chemistries. We have recently demonstrated that the combination of highly conductive inorganic solid electrolyte (ISE), Li0.33 La0.55 TiO3 (LLTO), with the mechanically durable solid polymer electrolyte (SPE), polyethylene oxide: Lithium bis(trifluoromethanesulfonyl)imide (PEO:LiTFSI), alongside a solid plasticizer, Succinonitrile, has proved to be successful in making highly performing polymer-rich (70% polymer) quaternary composite solid electrolytes (CSEs) that evade both the brittleness of ceramics and the poor conductivity of polymers. Herein, we extend the work to ceramic rich quaternary CSEs (70% ceramic). Ceramic-rich films were fabricated using tape casting technique and have reasonable ionic conductivity of 1.5 × 10 −4 S cm −1 at 55 °C, decent mechanical properties and displays impressive endurance in Li ∣∣ Li symmetrical cells (> 800 h). Solid-state coin-type cells assembled with composite cathode show satisfactory cycling performance at 0.05 C and 55 °C reaching specific discharge capacity of 160.6 mAh g −1, maintaining high Coulombic efficiency (> 95%) and high capacity retention of 90.3% after 30 cycles.